Switchable Adhesion in Vacuum Using Bio-Inspired Dry Adhesives - Purtov, Julia (ACS Appl Mater Interfaces, 2015)
[Image: see text] Suction based attachment systems for pick and place handling of fragile objects like glass plates or optical lenses are energy-consuming and noisy and fail at reduced air pressure, which is essential, e.g., in chemical and physical vapor deposition processes. Recently, an alternative approach toward reversible adhesion of sensitive objects based on bioinspired dry adhesive structures has emerged. There, the switching in adhesion is achieved by a reversible buckling of adhesive pillar structures. In this study, we demonstrate that these adhesives are capable of switching adhesion not only in ambient air conditions but also in vacuum. Our bioinspired patterned adhesive with an area of 1 cm(2) provided an adhesion force of 2.6 N ± 0.2 N in air, which was reduced to 1.9 N ± 0.2 N if measured in vacuum. Detachment was induced by buckling of the structures due to a high compressive preload and occurred, independent of air pressure, at approximately 0.9 N ± 0.1 N. The switch in adhesion was observed at a compressive preload between 5.6 and 6.0 N and was independent of air pressure. The difference between maximum adhesion force and adhesion force after buckling gives a reasonable window of operation for pick and place processes. High reversibility of the switching behavior is shown over 50 cycles in air and in vacuum, making the bioinspired switchable adhesive applicable for handling operations of fragile objects.